2005
DOI: 10.1038/sj.eye.6701988
|View full text |Cite
|
Sign up to set email alerts
|

How should blindness in children be managed?

Abstract: Background In all, 1.4 million children are estimated to be blind worldwide and only 6.5% of these are thought to come from the more affluent countries. The focus of this paper is therefore the developing world and Africa in particular, where evidence suggests that congenital cataract is becoming the leading cause of childhood blindness. Methods A review of the literature on management of congenital cataract was combined with original data from the author's experience in east Africa. Conclusions Health service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…In contrast, in some countries of SSA (Uganda, Tanzania and Nigeria), cataract is said to be overtaking corneal scarring as the major cause of childhood blindness, presumably due to the efforts of vitamin A supplementation [18,[20][21][22]. One study [23] in Mali examined the effect of starting vitamin A supplementation during National Immunization Days.…”
Section: Vitamin a Deficiencymentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, in some countries of SSA (Uganda, Tanzania and Nigeria), cataract is said to be overtaking corneal scarring as the major cause of childhood blindness, presumably due to the efforts of vitamin A supplementation [18,[20][21][22]. One study [23] in Mali examined the effect of starting vitamin A supplementation during National Immunization Days.…”
Section: Vitamin a Deficiencymentioning
confidence: 88%
“…It is estimated that 200 000 children are blind from cataract, and each year an additional 20 000-40 000 children are born with congenital cataract [29]. Recent studies [6,20,22,30] show that cataract may be overtaking corneal disease as the leading cause of avoidable BL/SVI in some countries of Africa. Even if surgery is available, the subsequent amblyopia resulting from poor follow-up remains a significant problem.…”
Section: Cataractmentioning
confidence: 97%
See 1 more Smart Citation
“…8 the current study has revealed a high prevalence of 4%. This seems to be even higher than the prevalances reported by other studies done in other developing countries like China.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The prevalence of childhood blindness worldwide is estimated to be around 0.07% and it is estimated to be about one-tenth that of adults. 3 However, a blind child suffers from more blind years than adults.…”
Section: Introduction Literature Review Prevalencementioning
confidence: 99%